Associations between positive and negative social experiences and epigenetic aging - Holly G. Prigerson; David Russell; Paul K. Maciejewski (Scientific Reports, 2025)
Abstract Associations between positive and negative social experiences and epigenetic aging are not well understood. To determine associations between positive and negative social experiences and epigenetic aging. Data from Midlife in the United States (MIDUS), a US population-based longitudinal cohort study, were used to examine relationships between social experiences and epigenetic aging. Participant reports of social experiences were assessed at survey waves closest to the subsequent collection of blood samples for DNA methylation testing and epigenetic clock calculation from 2004 to 2009 (MIDUS Core Sample) or 2012–2016 (MIDUS Refresher Sample). Analyses were conducted May 2024–June 2025. Self-reported positive (e.g., marriage, attendance at social meetings) and negative (e.g., parent’s drug problems, incarceration) social experiences were examined. Epigenetic was assessed from blood DNA methylation using the GrimAge and DunedinPACE epigenetic clocks. The sample (N = 1309) was 55.5% female, 22.5% Black and averaged 51.3 (SD = 12.5) years of age. In models adjusted for sociodemographic and health confounders, participants who reported positive social experiences such as being married (GrimAge: β = − 0.807, SE = 0.269, p < 0.01; Dunedin: β = − 0.022, SE = 0.007, p < 0.01) and engaging in social meetings (GrimAge β = − 1.027, SE = 0.250, p < 0.01; Dunedin: β = − 0.020, SE = 0.007, p < 0.01) exhibited significantly decelerated GrimAge scores; participants who reported negative social experiences such as a parent experiencing drug problems (GrimAge β = 2.430, SE = 0.761, p < 0.001), dropping out of school (GrimAge β = 2.869, SE = 0.405, p < 0.001; Dunedin β = 0.046, SE = 0.011, p < 0.001), and imprisonment (GrimAge β = 1.922, SE = 0.520, p < 0.001) exhibited significantly accelerated epigenetic aging scores. Adjusted models found the sum of positive social experiences was associated with decelerated epigenetic aging scores (GrimAge β = − 0.431, SE = 0.109, p < 0.001; Dunedin β = − 0.009, SE = 0.003, p < 0.01) and that the sum of negative social experiences was associated with accelerated epigenetic aging scores (GrimAge β = 0.934, SE = 0.162, p < 0.001; Dunedin β = 0.015, SE = 0.004, p < 0.01). Respondents with a “net positive” ratio of positive to negative social experiences had GrimAge scores that were 4.63 years younger on average than those with “net negative” social experiences (β = − 4.729; SE = 0.507; p < 0.001; adjusted β including covariates = − 2.847; SE = 0.469; p < 0.001). Associations of positive and negative social experiences with epigenetic aging were found to be independent of respondents’ perceived social support and their self-rated physical and mental health. Results suggest that negative social experiences accelerate while positive social experiences decelerate epigenetic aging. Negative and positive social experiences are each independently associated with epigenetic aging and net positive social experiences are associated with slower epigenetic aging.